2023
DOI: 10.1039/d3fo00531c
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of the bioactive components of sesame seeds and their impact on bone health issues in postmenopausal women

Abstract: Sesame seeds perform many therapeutic roles against many health issues especially related to bones because they possess rich contents of calcium, vitamins, proteins, oil, and carbohydrates. Using the PubMed, Science...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Although pharmacological options are available to counteract osteoporosis, considering the treatment duration for maintaining bone health during the postmenopausal period and the risks associated with the long-term use of estrogen therapy, it is clinically valuable to develop effective treatments with minimal side effects suitable for long-term use [17]. Therefore, dietary trends have been directed towards the utilization of health-protective and disease-preventive foods [18].…”
Section: Discussionmentioning
confidence: 99%
“…Although pharmacological options are available to counteract osteoporosis, considering the treatment duration for maintaining bone health during the postmenopausal period and the risks associated with the long-term use of estrogen therapy, it is clinically valuable to develop effective treatments with minimal side effects suitable for long-term use [17]. Therefore, dietary trends have been directed towards the utilization of health-protective and disease-preventive foods [18].…”
Section: Discussionmentioning
confidence: 99%
“…Only when the interaction between the two reaches a dynamic balance can the stability of the bone system be maintained (Kim et al., 2020). As the drugs for treating osteoporosis often have side effects, the anti‐osteoporosis ingredients in food are receiving increasing attention (Arooj et al., 2023; Su et al., 2022; Yue et al., 2022). Phytoestrogens are nonsteroidal compounds that are chemically similar to animal estrogens and can directly or indirectly bind to estrogen receptors, exhibiting certain estrogenic or anti‐estrogenic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Sesame seeds (Sesamum indicum L.) contain a multitude of phenolic compounds, which exhibit beneficial effects on human health. Phenolic components, known for their antioxidant, anti-inflammatory and hypolipidemic activities, and, specifically, sesame lignans like sesamin and sesamolin have attracted large interest regarding their nutritional benefits for humans in conditions such as atherosclerosis, hypertension, hyperlipidemia, obesity, diabetes, osteoporosis, arthritis and Alzheimer's disease [1][2][3][4][5][6][7][8]. A number of studies with sesame oil have reported a reduction in oxidative stress and an increase in vitamin E levels [9,10].…”
Section: Introductionmentioning
confidence: 99%